Teleworking in the context of the Covid-19 pandemic: advantages, disadvantages and influencing factors – the workers' perspective - Brandão, Sofia (2023)
Purpose – This study analyses workers' perceptions of the advantages and disadvantages of teleworking in the context of the Covid-19 pandemic, identifies factors that influence these perceptions, and verifies workers' intentions to maintain this work arrangement after the pandemic. Theoretical framework – By conducting a comprehensive literature review, we identified the advantages and disadvantages of teleworking and selected factors that have a significant influence over it. Design/methodology/approach – This is an exploratory and quantitative study, with primary data collection using a survey to identify the context of the teleworking experience and workers' perceptions of the advantages and disadvantages associated with this work arrangement. The sample obtained was 304 individuals. The data collected were processed using descriptive and inferential statistical analysis. Findings – The teleworking experience was essentially positive. Most workers intend to maintain this arrangement after the pandemic. The conditions offered by the organizations and the existence of an adequate workspace at home were factors that strongly influenced workers' perceptions of the advantages and disadvantages of teleworking. Practical & social implications of research – Considering workers' perceived benefits and willingness to remain teleworking, organizations should implement and manage teleworking programs with the understanding that organizational factors greatly influence the teleworker's experience and are critical to the success of this practice. Originality/value – This study provides additional data concerning the teleworking experience during the Covid-19 pandemic and, to the best of our knowledge, it is one of the first studies to focus on the perception of Portuguese workers regarding the advantages and disadvantages of teleworking and to identify influencing factors. Keywords – teleworking; telecommuting; Covid-19; advantages; disadvantages